ThunderSTORM: a comprehensive ImageJ plug-in for PALM and STORM data analysis and super-resolution imaging - Ovesný, Martin; Křížek, Pavel; Borkovec, Josef; Svindrych, Zdeněk; Hagen, Guy M (Bioinformatics (Oxford, England), 2014)
UNLABELLED: ThunderSTORM is an open-source, interactive and modular plug-in for ImageJ designed for automated processing, analysis and visualization of data acquired by single-molecule localization microscopy methods such as photo-activated localization microscopy and stochastic optical reconstruction microscopy. ThunderSTORM offers an extensive collection of processing and post-processing methods so that users can easily adapt the process of analysis to their data. ThunderSTORM also offers a set of tools for creation of simulated data and quantitative performance evaluation of localization algorithms using Monte Carlo simulations. AVAILABILITY AND IMPLEMENTATION: ThunderSTORM and the online documentation are both freely accessible at https://code.google.com/p/thunder-storm/.
Keywords: fluorescenční mikroskopie; mikroskopie; algoritmy; počítačová grafika; Image Processing, Computer-Assisted; Software; software; Algorithms; počítačové zpracování obrazu; Microscopy; Monte Carlo Method; Computer Graphics; metoda Monte Carlo; Microscopy, Fluorescence